Podoby vizuální propagandy v německém zázemí za první světové války - Beer, Kamil (Lidé města, 2020)
One of the popular perceived notions of the German Reich’s defeat during the First World War is that propaganda, its misuse or insufficient use, was one of the reasons for the empire’s collapse. This is not so, as per the words of American professor David Welch and German professor Klaus- Jürgen Bremm, the German propaganda machinery was one of the most sophisticated during the war and maintained the Reich as a formidable adversary of the Entente powers for almost five years of the war. The article explores the history of Germany’s war propaganda establishment and mentions its noteworthy visual expressions on home front posters and its main “talking points”. Its other notable visual outlets are also described: e.g. the “nail men” or the growing movie industry. When fitting, the article also mentions the reception of propaganda. German propaganda was based not only on a strong national “network” of public opinion offices, but it also used types of imagery powerful enough to convince the German people to continuously contribute to the war effort. However, it had its shortcomings and in time, as the conflict became too long and taxing on the populace, the effect of propaganda waned, and the Reich was eventually defeated by the Entente powers.